Effects of High Order Modification of Work Head Setting on Tooth Flank Form and Contact Zone of Spiral Bevel Gear - Huang Gang; Zhang Weiqing; Guo Xiaodong; Wang Ge; Wen Yikai (Jixie chuandong)
Based on the generating theory of the pinion of spiral bevel gears and the relative motion theory,the tooth flank equation with the work head setting high order modification formula is established. According to the manufacturing parameters of the working gear flank of a spiral bevel gear set,a program is written on the platform of Matlab to calculate the modified tooth flank coordinates. Through constructing tooth flank form error figures and computing contact zones of the calculated tooth flank,the effects of work head setting high order modification on tooth flank form and contact zone of spiral bevel gears are analyzed,which can provide theoretical basis and valuable reference to facilitate the control of tooth flank form and contact zone of spiral bevel gear.